Constructivist Assessment Approaches in Science Pre-service Teacher Education Programme - Dogra, Bharti (SCHOOL SCIENCE, 2015)
Constructivist assessment approaches are based on the basic principles of the theory of constructivism. According to constructivism, learners construct knowledge through observation, experience, documentation, analysis and reflection (Dogra, 2010). According to the constructivist perspective, teaching or rather more precisely learning of science is not a search for the ultimate truth. It is a process which is of utmost importance in science than the content (Dogra, 2010). Assessment from constructivist perspective is a holistic process, which includes both content as well as process. Constructivist assessment is based on the collaborative activities of a teacher as well as learners. Constructivist assessment is subjective because it makes use of different qualitative strategies rather than quantitative ones. For implementing constructivist assessment approaches, the teacher needs to know the students well. This paper exemplifies how different constructivist assessment approaches can be used in science pre-service teacher education programme. The use of various constructivist assessment approaches, like roleplay, story writing, concept maps, student presentations and poster projects in school life experience comprise the pre-service teacher education programme of the Army Institute of Education, Delhi Cantonment (a B.Ed. college affiliated to the I. P. University), which find a detailed mention in this paper. Pre-service science teachers designed constructivist assessment tasks in collaboration with the author. Some of the examples of constructivist assessment approaches experienced by secondary school science students are presented in this paper. This paper exemplifies how assessment forms an integral component of learning and also an enjoyable and fun-filled activity for both pre-service science teachers as well as school students. Pre-service science teachers felt that such assessment approaches made students involved in their assessment and shifted the focus from tests to more subjective assessment tasks.